Névoas & Cristais: recriação tecnológica e estudo performático - Leite, Daniela dos Santos (2013)
This research paper describes the process of recreation of the technological part and the performance of the piece Névoas & Cristais by Jônatas Manzolli. Created in 1995, this piece represents an important marker in the history of Brazilian compositions for a percussion instrument with technological support, because it was the first composition by a Brazilian for vibraphone and live electronics in which computerized control was used. However, the incompatibility of the devices and software used at that time with current technology made its performance unviable. For this reason, with the objective of remaking a performance of the piece, adaptations of the electronic devices used and the recreation of the technological part with current equipment and software were necessary. The methodology used was taken from bibliographic research which generated a retrospective history about the development of technology and its use in the artistic and musical industries, as well as a reflection on the permanence of pieces mediated by technology. After that, through the study of an article written by the compositor, and analysis via listening of the recording made with the original programming by percussionist André Juarez, we recreated the technological part using the software PureData and described the strategies adopted. With the new programming, it was possible to carry out once more the performance of the piece and develop a comparative study between the recording made by André Juarez and the recording obtained with the new programming. We finished with a reflection on the work produced and the importance of the recovery of musical pieces mediated by technology. We concluded, through comparative analysis, that the initial objectives were achieved, as it was possible to recreate the technological part of the piece using current devices and software, generating sound results similar to those of the 1995 programming.